Planetary boundaries: Guiding human development on a changing planet - Steffen, W.; Richardson, K.; Rockström, Johan; Cornell, S.E.; Fetzer, I.; Bennett, Elena M.; Biggs, R.; Carpenter, Stephen R.; Vries, W. de; Wit, C.A. de; Folke, C.; Gerten, D.; et al. (American Association for the Advancement of Science, 2015)
The planetary boundaries framework defines a safe operating space for humanity based on the intrinsic biophysical processes that regulate the stability of the Earth System. Here, we revise and update the planetary boundaries framework, with a focus on the underpinning biophysical science, based on targeted input from expert research communities and on more general scientific advances over the past 5 years. Several of the boundaries now have a two-tier approach, reflecting the importance of cross-scale interactions and the regional-level heterogeneity of the processes that underpin the boundaries. Two core boundaries—climate change and biosphere integrity—have been identified, each of which has the potential on its own to drive the Earth System into a new state should they be substantially and persistently transgressed.